Diagnostic et inventaire du cancer du sein dans la Wilaya de Souk Ahras - GUERGAH Nesrine; KHALDI Chadia (My University, 2016)
In Algeria, breast cancer represents 50% of gynecological cancers. It’s the 2 nd in the region of Souk Ahras after pneumonic cancer. A statistical study has been realized, using data from the hospital of Ibn Rochd (State of Souk Ahras) to determine the main risk factors that causes this disease. The class of age the most touched by this disease in 41cases is between 40 and 45, with predominance of histological type infiltrant canalic carcinoma(34%). And according to histopronostic classification (SBR), there is a predominance of the 2 nd grade (59%), the measures of tumors are restricted between 2 and 5 cm, besides the highest percentage of risk factor was obesity amongst menopause women (73%). These results mean that breast cancer in the region is diagnosed at an advanced stage, and it can be late, because of the rejection of patients for accepting mastectomy. The resort of patients for traditional treatments in first place, and the non respect of consultation and surveillance are the first causes of this disease. ---------------------------------------------------------------------------------------- من سرطانات الأمراض النسائیةّ . يعتبر الثاني في ولاية سوق أهراس بعد سرطان % 50 في الجزائر؛ یمثل سرطان الثدي الرئتين. تم تحقیق دراسة إحصائیة اعتمادا على بیانات مستشفى ابن رشد من اجل تحدید عوامل الخطر المسببة للمرض. الفئة العمریة الأكثر عرضة من بین 41 حالة كانت محصورة بین 40 و 45 سنة ، مع سيادة سرطان الثدي الغددي للقنوات المفرزة ؛ أطوال الأورام محصورة بین 2 و 5 سم ؛ (%59) هناك سيادة للرتبة 2 للمرض SBR. حسب التقسيم النسيجي (%34) . (% (73 إضافة إلى أن عامل الخطر الأكثر نسبة ھو السمنة لدى النساء البالغات سن الیأس النتائج تثبت أن تشخیص المرض في المنطقة یكون متطورا و متأخرا بسبب رفض المریضات بتر العضو. رجوع المرضى إلى وسائل العلاج التقلیدیة؛ و عدم استشارة الأطباء و متابعة المرض ھي الأسباب الأولى لھذا المرض . ----------------------------------------------------------------------------------------- En Algérie, le cancer du sein représente 50% des cancers gynécologiques. C'est le 2 ème la région de Souk Ahras après un cancer pneumonique. Une étude statistique a été réalisé, à partir des données de l'hôpital Ibn Rochd (Etat de Souk Ahras), pour déterminer les principaux facteurs de risque à l'origine de cette maladie. La classe d'âge la plus touchée par cette maladie dans 41 cas se situe entre 40 et 45 ans, avec une prédominance du carcinome canalique infiltrant de type histologique (34 %). Et selon la classification histopronostique (SBR), il y a une prédominance du 2 ème grade (59%), les mesures des tumeurs sont limitées entre 2 et 5 cm, et le pourcentage le plus élevé de facteur de risque était l'obésité chez les femmes ménopausées (73%). Ces résultats signifient que le cancer du sein dans la région est diagnostiqué à un stade avancé. stade, et il peut être tardif, en raison du refus des patientes d'accepter une mastectomie. Le recours des patients aux traitements traditionnels en premier lieu, et le non respect de la consultation et de la surveillance sont les premières causes de cette maladie.